(E)-1-(2-Hydroxy-4,6-dimethoxyphenyl)-3-(4-methoxyphenyl)prop-2-en-1-one from Kaempferia rotunda Val - Sirat, H.M.; Feng, Y.S.; Hazni, H.; Awang, K.; Ng, S.W. (International Union of Crystallography, 2010)
The planar -CH=CHC(=O)- fragment (r.m.s. deviation = 0.074 angstrom) in the title compound, C18H18O5, connects the planar hydroxydimethoxyphenyl (r.m.s. deviation = 0.039 angstrom) and methoxylphenyl (r.m.s. deviation = 0.021 angstrom) parts. The central fragment forms a dihedral angle of 13.7 (1)degrees with the hydroxydimethoxyphenyl part and 32.0 (1)degrees with the methoxyphenyl part. The hydroxy group forms an intramolecular hydrogen bond to the carbonyl O atom.